2010
DOI: 10.1016/j.parkreldis.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Tests of dorsolateral frontal function correlate with objective tests of postural stability in early to moderate stage Parkinson’s disease

Abstract: A substantial number of individuals with Parkinson’s disease who display impaired postural stability experience accelerated cognitive decline and an increased prevalence of dementia. To date, studies suggest that this relationship, believed to be due to involvement of nondopaminergic circuitry, occurs later in the disease process. Research has yet to adequately investigate this cognitive-posturomotor relationship especially when examining earlier disease states. To gain greater understanding of the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 28 publications
4
28
0
4
Order By: Relevance
“…33,34 Cognitive tests specific to prefrontal function have been significantly associated with postural stability in patients with early to moderate PD. 35 Thus, the associations between both stride length and walking speed and cognitive processing speed revealed in this study may potentially be accounted for by shared white matter networks connecting frontal and parietal regions, and the association between executive function and step width variability may be due to overlapping systems in the prefrontal cortex.…”
Section: Cognitive and Gait Performance In Parkinson Diseasementioning
confidence: 74%
“…33,34 Cognitive tests specific to prefrontal function have been significantly associated with postural stability in patients with early to moderate PD. 35 Thus, the associations between both stride length and walking speed and cognitive processing speed revealed in this study may potentially be accounted for by shared white matter networks connecting frontal and parietal regions, and the association between executive function and step width variability may be due to overlapping systems in the prefrontal cortex.…”
Section: Cognitive and Gait Performance In Parkinson Diseasementioning
confidence: 74%
“…Indeed, impaired executive function and attention are related to postural instability in PD [5]. Further, "dual tasking," or the simultaneous performance of motor and/or cognitive tasks, compounds decrements in motor and cognitive performance [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The connections between the dorsolateral prefrontal cortex and the basal ganglia are suggested to cause working memory deficits in people with IPD. 31 The authors suggested that postural stability in people with IPD may reduce as cognitive function declines; however, this study was a preliminary investigation and further research in this area is warranted.…”
Section: Discussionmentioning
confidence: 85%
“…In one study, Nocera, et al 31 investigated whether reduced function of the dorsolateral prefrontal area affected postural stability in people with mild to moderate stages of IPD (Hoehn and Yahr stages 1-2.5), by using the three selected tests for cognitive tasks to activate the dorsolateral prefrontal area (Digit Span Backward Subtest from Wechsler Memory Scale, Controlled Word Association Test, and Stroop Colour Word Test) and the Mini-Mental State Examination (MMSE) for general evaluation of the degree of cognition. The study demonstrated a significant, moderate negative correlation between COP displacement area and reduced cognitive ability (P,0.05).…”
Section: The Effect Of Stiffnessmentioning
confidence: 97%
See 1 more Smart Citation